Posterior Arm Perforator Flap for Axillary Reconstruction After Hidradenitis Suppurativa Excision. Issue 3 (August 2019) - Sirvan, Selami Serhat; Demir, Isil Akgun; Irmak, Fatih; Sevim, Kamuran Zeynep; Dagdelen, Daghan; Yazar, Sevgi Kurt; Karsidag, Semra
Introduction: Hidradenitis suppurativa (HS) is a chronic inflammatory disease arising from the hair follicles in apocrine gland-rich areas. It is also one of the most common indications for axillary surgery. Reconstruction of the axillary region after such surgery must be performed meticulously due to its critical location and crucial content. In this report, we present our experience of reconstruction of axillary defects with posterior arm perforator flaps (PAPF) following radical excisions. Methods: A total of 14 patients (9 male, 5 female) aged between 16 and 49 years who had presented with HS in the axillary region and, after surgery, underwent reconstruction with either island or skin bridge posterior arm flap between January 2015 and October 2016 were included in the study and evaluated retrospectively. All of the defects were reconstructed with PAPF following wide excision. Results: Five of the flaps (over 4 patients) were designed as flaps with skin bridges, while the remaining 12 flaps in 11 patients were raised as island flaps. The flaps had areas ranging from 20 to 84 cm 2 (mean 39.5 cm 2 ), depending on the size of the defect after excision. The mean follow-up time after the operation was 6 months. Wound dehiscence was detected in one patient, and another patient developed marginal necrosis during the postoperative period; no other complications were observed. Conclusion: Posterior arm perforator flaps can provide sufficient amounts of soft tissue to cover axillary defects and should be considered as the flap of choice in axillary reconstruction.